Sulfur‐Grafted Hollow Carbon Spheres for Potassium‐Ion Battery Anodes. Issue 30 (3rd June 2019) - Ding, Jia; Zhang, Hanlei; Zhou, Hui; Feng, Jun; Zheng, Xuerong; Zhong, Cheng; Paek, Eunsu; Hu, Wenbin; Mitlin, David
Abstract: Sulfur‐rich carbons are minimally explored for potassium‐ion batteries (KIBs). Here, a large amount of S (38 wt%) is chemically incorporated into a carbon host, creating sulfur‐grafted hollow carbon spheres (SHCS) for KIB anodes. The SHCS architecture provides a combination of nanoscale (≈40 nm) diffusion distances and CS chemical bonding to minimize cycling capacity decay and Coulombic efficiency (CE) loss. The SHCS exhibit a reversible capacity of 581 mAh g −1 (at 0.025 A g −1 ), which is the highest reversible capacity reported for any carbon‐based KIB anode. Electrochemical analysis of S‐free carbon spheres baseline demonstrates that both the carbon matrix and the sulfur species are highly electrochemically active. SHCS also show excellent rate capability, achieving 202, 160, and 110 mAh g −1 at 1.5, 3, and 5 A g −1, respectively. The electrode maintains 93% of the capacity from the 5th to 1000th cycle at 3 A g −1, with steady‐state CE being near 100%. Raman analysis indicates reversible breakage of CS and SS bonds upon potassiation to 0.01 V versus K/K + . The galvanostatic intermittent titration technique (GITT) analysis provides voltage‐dependent K + diffusion coefficients that range from 10 −10 to 10 −12 cm 2 s −1 upon potassiation and depotassiation, with approximately five times higher coefficient for the former. Abstract : A sulfur‐grafted hollow‐carbon‐spheres anode with high sulfur content of 38 wt% is created and utilized for potassium‐ion storage. The unique architecture combining nanoscale ion‐diffusion distances and CS covalent bonding endows the anode with record‐high specific capacity and energy density contribution.